Enhancing Ethical Values in Language Pedagogy: Lessons from Gowe Tugalaoyo (Judgment Stone) in Siwawo Village - Bawamenewi, Arozatulo; Riana, Riana (PT. Riset Press International, 2024)
In the era of the ancestors of the Nias people, the majority adhered to ritual beliefs by facing and prostrating to ask for guidance on the truth through menhirs or the like that are believed and agreed upon by a group of people. The purpose of this research is to describe the genealogy and reveal the value of honesty contained in the Tugala Oyo Gowe (judgment stone) located in Siwawӧ Village, Tugala Oyo Sub-district, North Nias Regency. This research method is descriptive research by applying the observation method through an ethnographic approach. To obtain information about the meaning of rituals contained in gowe (judgment stone) through figures and residents. Data collection techniques are carried out through interviews, observations, field notes and documentation while data analysis techniques are formulated by paying attention to the stages of activity, namely qualitative structuring of raw data, data selection. Furthermore, in collecting data this research used the original Nias language of the informants and then translated into bilingualism. The qualitative approach in question is to explain the data related to community views on the value of honesty towards the object being observed, namely gowe Tugala Oyo. The character value of respecting one's own culture is very important to instill in children so that cultural resistance can be maintained for generations. Cultural values such as religion, morals, cooperation, trust, and responsibility should be used as a philosophical foundation in people's lives. The character of upholding ancestral dynasties is a characteristic of someone who remains steadfast